1999
DOI: 10.1093/emboj/18.4.1003
|View full text |Cite
|
Sign up to set email alerts
|

In vivo expression of the nucleolar group I intron-encoded I-DirI homing endonuclease involves the removal of a spliceosomal intron

Abstract: The Didymium iridis DiSSU1 intron is located in the nuclear SSU rDNA and has an unusual twin-ribozyme organization. One of the ribozymes (DiGIR2) catalyses intron excision and exon ligation. The other ribozyme (DiGIR1), which along with the endonuclease-encoding I-DirI open reading frame (ORF) is inserted in DiGIR2, carries out hydrolysis at internal processing sites (IPS1 and IPS2) located at its 3Ј end. Examination of the in vivo expression of DiSSU1 shows that after excision, DiSSU1 is matured further into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(84 citation statements)
references
References 50 publications
8
76
0
Order By: Relevance
“…GIR1-dependence of endonuclease expression from the intact intron+ A: Schematic drawing depicting the PCR-based endonuclease assay+ A PCR product is incubated with extract+ If endonuclease is present, it cleaves the substrate, producing the unique five-base 39 overhangs specific to the Naegleria NaSSU1 endonuclease+ A double-stranded oligonucleotide (indicated by dark bars) with overhangs complementary to one of the products is added and can be ligated to a cleavage product+ The resulting DNA is amplified by PCR+ Small arrows represent primers+ B: Results of PCR based I-NjaI assay+ Lanes 1 and 11: 100-bp ladder; lanes 2-4: 50, 25, or 5 mg, respectively, of total protein from galactose-induced cells carrying the wild-type plasmid pYGal-NjaSSU; lanes 5-7 and 8-10: 50, 25, or 5 mg, respectively, of total protein from independently transformed, galactose-induced cells carrying the GIR1-crippled plasmid pYGal-G1 Ϫ Nja+ The specific product for the hybrid is indicated by the arrow+ An ;750-bp band in each lane (indicated by a circle on the right) is a PCR artifact+ the intron-homing endonuclease+ To address this hypothesis, we have examined intron-RNA processing in N. gruberi, a host organism for NaSSU1+ The data presented here show that in vivo cleavage also occurs just upstream of the ORF, at both the IPS1 and the IPS2 sites identified in vitro+ As primer extension showed only the 59 end corresponding to IPS2, the sequential self-cleavages reported by Einvik and colleagues (1998b) in vitro must occur very efficiently in Naegleria+ A result similar to ours was obtained in the analysis of DiSSU1 in its host organism D. iridis (Vader et al+, 1999)+…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…GIR1-dependence of endonuclease expression from the intact intron+ A: Schematic drawing depicting the PCR-based endonuclease assay+ A PCR product is incubated with extract+ If endonuclease is present, it cleaves the substrate, producing the unique five-base 39 overhangs specific to the Naegleria NaSSU1 endonuclease+ A double-stranded oligonucleotide (indicated by dark bars) with overhangs complementary to one of the products is added and can be ligated to a cleavage product+ The resulting DNA is amplified by PCR+ Small arrows represent primers+ B: Results of PCR based I-NjaI assay+ Lanes 1 and 11: 100-bp ladder; lanes 2-4: 50, 25, or 5 mg, respectively, of total protein from galactose-induced cells carrying the wild-type plasmid pYGal-NjaSSU; lanes 5-7 and 8-10: 50, 25, or 5 mg, respectively, of total protein from independently transformed, galactose-induced cells carrying the GIR1-crippled plasmid pYGal-G1 Ϫ Nja+ The specific product for the hybrid is indicated by the arrow+ An ;750-bp band in each lane (indicated by a circle on the right) is a PCR artifact+ the intron-homing endonuclease+ To address this hypothesis, we have examined intron-RNA processing in N. gruberi, a host organism for NaSSU1+ The data presented here show that in vivo cleavage also occurs just upstream of the ORF, at both the IPS1 and the IPS2 sites identified in vitro+ As primer extension showed only the 59 end corresponding to IPS2, the sequential self-cleavages reported by Einvik and colleagues (1998b) in vitro must occur very efficiently in Naegleria+ A result similar to ours was obtained in the analysis of DiSSU1 in its host organism D. iridis (Vader et al+, 1999)+…”
Section: Discussionsupporting
confidence: 84%
“…Under conditions used to force homing of PpLSU3 into yeast rDNA (Muscarella & Vogt, 1993;Lin & Vogt, 1998), NaSSU1 failed to home successfully in yeast+ PCR analysis did not detect any intact introns in rDNA+ However, this analysis did provide evidence of rare intron-exon junction fragments, suggesting that homing at least had been initiated+ Either gene conversion then failed to proceed to completion, or after gene conversion was completed at least in some rDNA copies, the introns were deleted or partially deleted because of deleterious effects on cell growth+ The latter possibility is more likely: we showed that when NaSSU1 was artificially built into a plasmid-born rDNA, preribosomal RNA expression from the plasmid was not able to rescue cell growth in the absence of RNA polymerase I transcription of the rDNA copies on chromosome XII (data not shown)+ It is possible that this failure is because of lack of splicing, or inefficient or incorrect splicing+ Alternatively, the intron might affect some other aspect of ribosomal RNA maturation+ The latter possibility is suggested by the observation that the Tetrahymena intron inserted into the ribosomal RNA genes of Schizosaccharomyces pombe prevented proper maturation of the 5+8S species, despite the absence of obvious splicing defects (Good et al+, 1994)+ Presumably group I introns in nuclear rDNA have coevolved with rDNA to maximize splicing efficiency and to minimize disruption of other processes in their host organisms+ It seems possible that minor sequence changes might allow them to adapt to new species, but this notion has not been tested experimentally+ To study NaSSU1 splicing, processing, and endonuclease expression in yeast, we developed a strategy that circumvented the lack of homing in this system+ First, the endonuclease was expressed by itself from a plasmid, and among surviving colonies, a mutant yeast strain was identified that tolerates endonuclease activity+ This strain had acquired a single mutation in the endonuclease target site in all the rDNA copies, analogous to the mutations described previously that confer resistance to the I-PpoI endonuclease in yeast (Muscarella & Vogt, 1993;Lin & Vogt, 1998)+ Into this strain a plasmid was introduced that carries NaSSU1 with ;0+3 kb flanking rDNA 59 exon and 39 exon sequences, under control of the GAL1 promoter+ Induction by galactose in this system led to the synthesis of an rRNA from which the intron spliced and further processed itself, in a manner similar to that seen in vitro and also in Naegleria+ Furthermore, intron expression led to endonuclease activity, which could be detected in crude extracts either by a straightforward DNAcleavage assay, or by a more sensitive PCR-based assay for the characteristic 5 nt sticky end produced by cleavage+ An inactivating mutation in the NaGIR1 ribozyme abrogated endonuclease activity+ This result thus supports the hypothesis that the function of NaGIR1 is to generate the mRNA for the Naegleria endonuclease+ NaSSU1 and DiSSU1 are the only known examples of twin-ribozyme group I introns+ Despite differences in organization (Einvik et al+, 1998a), comparison of processing reveals a number of shared features+ First, in both the DiSSU1 and NaSSU1 systems, a GIR1-mediated cleavage is observed in vivo downstream of the ORF+ Second, both DiSSU1 RNA (Vader et al+, 1999) and NaSSU1 RNA form full-length circles in their host organisms+ Circularization, like 39 SS hydrolysis, is usually thought to be a side reaction of...…”
Section: Results)+supporting
confidence: 59%
See 2 more Smart Citations
“…Here we suggest that the K-motif in P9.2 represents a key regulatory element between the reaction pathways, and that a protein factor may exists in the Didymium nucleus that participates in the regulation. The observation that splicing appears much more efficient than hydrolysis in vivo compared to in vitro [8,[12][13][14] is consistent with this proposal.…”
Section: Functional Implications Of P92 In Hydrolysissupporting
confidence: 86%